IMPLEMENTASI AKUNTANSI PADA UMKM SERTA IMPLIKASINYA TERHADAP KUALITAS INFORMASI DAN PENGAMBILAN KEPUTUSAN - Hadi Purwanto; Rita Rita (Institut Teknologi dan Bisnis Swadharma, 2021)
The purpose of the study was to obtain an overview of the accounting practices applied to CV. X and knowing the reasons behind its implementation and knowing the implications of the application of these accounting practices on the quality of information produced by CV. X . This research is a type of qualitative research with a case study approach. The subjects in this study are medium-scale MSMEs in the Pasuruan area which are engaged in the concentrate block industry. Sources of data used in this study are secondary and primary data. Data collection methods used include observation, interviews, documentation of literature studies and Web studies. This study uses a descriptive technique to analyze the data. The results of this study stated that accounting practices in CV. X. has not fully referred to SAK ETAP. Although it has been able to prepare a number of financial reports according to the mandate of ETAP, CV.X has not been able to implement accounting according to standards properly. This is based on various factors including the environment, the lack of competence of the company's human resources, weaknesses in the company's control system and the lack of rules and regulations from the government. As a result, the company failed to meet the qualitative requirements of information quality. However, this does not affect the company to produce quality information. Poor accounting practices at CV.X apparently did not significantly affect the decision-making process.